Light Hydrocarbon Geochemistry of Oils in the Alpine Foreland Basin: Impact of Geothermal Fluids on the Petroleum System. (17th September 2017) - Pytlak, Ł.; Leis, A.; Prochaska, W.; Sachsenhofer, R. F.; Gross, D.; Linzer, H.-G.
Abstract : Oil is produced in the Austrian sector of the Alpine Foreland Basin from Eocene and Cenomanian reservoirs. Apart from petroleum, the basin hosts a significant geothermal potential, which is based on the regional flow of meteoric water through Malmian (Upper Jurassic) carbonate rocks. Oils are predominantly composed of n -alkanes, while some samples are progressively depleted in light aromatic components. The depletion in aromatic components relative to abundant n -alkanes is an effect of water washing. Waters coproduced with oils that are affected by water washing show a progressive reduction in salinity and depletion in 2 H and 18 O isotopes, indicating that the degree of water washing is mainly controlled by the inflow of meteoric water from the Malmian aquifer. In some fields with Cenomanian reservoir rocks, a hydraulic connectivity with the Malmian aquifer is evident. However, water washing is also recognized in Eocene reservoirs and in areas where the Malmian aquifer is missing. This shows that existing flow models for the regional Malmian aquifer have to be modified. Therefore, the results emphasize the importance of combining data from the petroleum and geothermal industry, which are often handled separately.